Is There any Important Difference Between Ranitidine Bismuth Citrate and Ranitidine at Helicobacter Pylori Eradication and Ulcer Healing ? (Annals of Medical Research, 2021)
None
Keywords: Helicobacter pylori eradication,ulcer, Ranitidine, Ranitidine bismuth citrate.